Serum testosterone levels in type 2 diabetes mellitus - Kundu, Dipankar; Ghosh, Enakshi; Sinha Roy, Suparna; Basu, Satyaki (International Journal of Medical Research and Review, 2018)
Introduction: Diabetes mellitus is a multifactorial disease which is characterised by hyperglycaemia, dyslipidaemia, involves various organ systems, and results in various long-term complications. Several studies have suggested that men with low testosterone levels are at a greater risk of developing type 2 diabetes mellitus, and that low testosterone levels may even predict the onset of diabetes. Recent studies have shown that a low serum testosterone level is strongly associated with an increased likelihood of the metabolic syndrome. Aim: To compare the serum total testosterone levels in type 2 diabetes mellitus patients with that of non-diabetic healthy controls. Material and Methods: The study was conducted in OPD of Medical College, Kolkata. In the present study 50 men aged 35-55 years who were diagnosed as type 2 diabetes mellitus patients and confirmed by the estimation of fasting plasma glucose (≥126mg/dl), post prandial blood glucose (≥200mg/dl) and HbA1C (≥6.5%) were selected, 50 healthy age and BMI matched individuals, were selected as controls. Patients with a known history of hypogonadism, panhypopituitarism, hyperthyroidism, patients taking exogenous testosterone and glucocorticoids, patients suffering from chronic debilitating disease, such as renal failure, cardiac failure, liver cirrhosis, or HIV, were excluded from the study. The laboratory investigations included evaluation of serum testosterone levels, fasting and postprandial blood glucose, with the levels of HbA1c and Creatinine. Statistical analysis was performed using SPSS 20.0. Results are represented as mean±SD and number (%). Pearson’s correlation test was performed to measure the linear dependence of the study parameters. Results: Serum Total Testosterone level of diabetic group was 3.51±1.26ng/ml, which was found significantly lower than control group with serum total testosterone level 5.88±2.34ng/ml, (p-value < 0.0001). Conclusion: This study has shown that there is a significant reduction in serum total testosterone levels in type 2 diabetes mellitus patients.